Effect of Experimental Palatal Prosthesis on Voice Onset Time. Issue 3 (2nd August 2016) - Hattori, Mariko; Sumita, Yuka I.; Elbashti, Mahmoud E.; Kurtz, Kenneth S.; Taniguchi, Hisashi
Abstract: Purpose: Objective evaluation of a patient's speech is needed in prosthetic dentistry because the prostheses can affect the intelligibility of speech. Measurement of voice onset time is one evaluation method of consonant production used in phonetic science. The purpose of this study was to confirm the influence of a palatal prosthesis on consonant production by measuring voice onset time. Materials and Methods: In this study, voice onset time was measured in 10 healthy women (mean age 26.5 years) under two conditions: with and without an experimental palatal prosthesis. In this study, voice onset time of /ta/ and /ka/ were used to determine the effect of wearing a palatal prosthesis; /pa/ was tested as a control, with the null hypothesis that voice onset time of /ta/ and /ka/ would not change when wearing a palatal prosthesis. Results: Medial voice onset time of /pa/, /ta/, and /ka/ syllables without the palatal prosthesis was 22.5 ms, 19.5 ms, and 42.5 ms, whereas that with the palatal prosthesis was 22.5 ms, 23.5 ms, and 55.0 ms. Voice onset times for /ta/ and /ka/ were prolonged when wearing the experimental palatal prosthesis, whereas /pa/ showed no significant difference. Conclusion: Consonant production was affected by wearing a palatal prosthesis, and this change in sound was detected by measuring voice onset time.